Peningkatan Produktivitas Pada Sub Produksi Bottom Cabinet Washing Machine 2 Tabung - Jonathan Adriel Junaedi, Tan; Iwan Halim Sahputra (Jurnal Titra, 2023)
PT. Hartono Istana Teknologi is a company that produces electronic goods and home appliances, one of which is a washing machine. Manufacturing of washing machines is done by way of assembly. The analysis aims to identify waste that exist in the production process, which will be carried out by eliminating waste and balancing the production line so that the distribution of workload can be evenly distributed and increase the line efficiency as well as operator productivity. The method used is 7 wastes method and also line balancing using the Killbridge Wester method. In knowing the balance of the line, it can be done by calculating the line efficiency, balance delay, smoothness index and total of idle time. The proposed improvements are obtained by reducing the waste of waiting and waste of motion that caused by the uneven distribution of workloads and the layout of material placement that are far from the operator's reach. From the results of this proposed improvement, the line efficiency increase from 84% to 90%, increase productivity by 2%, reduce balance delay from 16% to 10% and idle time from 22.9 seconds to 14.6 seconds.